Gender and Development: A Literature Review - Marie Correa-Fernandes; Brandon K. Dumas; Chanika Jones; Victor Mbarika; Isaac M. Ong'oa (Centre for Behaviour and Wellness Advocacy, 2015)
This paper explores the literature on gender and development. Achieving women development requires the considerations of various aspects. Education is an important factor of development but it must be tailored to meet the needs of the target group. In developing countries one of the main barriers to women development is early marriage, which prevents further education, physical growth and power of decision; thus leads to more disparities between men and women. The interpretation of religious beliefs is another factor that legitimates inequalities; organizations have to understand its meaning and find ways to implement development programs in faith-based environments. They also have to advocate change in institutions that sustain disparities for the creation of unbiased policies.